The Industrial Revolution And State - عمران , مقداد (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The current research addresses the state as a topic to be studiedas it is a result of social and historical circum stances that affect its presense and taskThisresearch also aims to reveal the starts social-bilty. The English industrial revolution represent The variables of the research as it is the social and historical condition that generated a new form of the country and new functionsFierst the research tachles the social reasons and consequences of the industrial revolution.It also portrays the varied social conditions in England lcike the feudal systemand economical .One where the agricultural in frastructure formed the base of possession.The political one represented by the 1866 revolution in that period with the political economical and social consequences represent ed by representative parliamentary state , the private property and appearance of industurial bourgeoisieThen it tackles the states new form at hobbis whi considers the state as an essential social necessity to move into the civil status ,and to abolish the state of every man against every man and john locke who considers the state as an economical necessity at first place with an optimistic visionIn, in addition to Rousseau and the general will perspective which distinguished hisbeliefs ,about the state the outcome and the recomme ndation that the sociability of the state represented by the social contract that created it andthat it the out put of the historical and social condition that ful fill it,s sociability